2006
DOI: 10.1021/es060537y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Fractal Properties of Particles Emitted from Spark Ignition Engines

Abstract: Size, morphology, and microstructure of particles emitted from one light-duty passenger vehicle (Buick Century; model year 1990; PM (particulate matter) mass emission rate 3.1 mg/km) and two light-duty trucks (Chevrolet C2; model year 1973; PM mass emission rate 282 mg/km, and Chevrolet El Camino; model year 1976; PM mass emission rate 31 mg/km), running California's unified driving cycles (UDC) on a chassis dynamometer, were studied using scanning electron microscopy (SEM). SEM images yielded particle propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
7
39
0
Order By: Relevance
“…Studies of particle morphology using electron microscopes have shown that individual particles emitted from diesel and spark-ignition engines exhibit fractal-like characteristics [59,60]. However, specific parameters of the fractal-like particles, such as fractal dimension and radius of gyration, are widely variable dependent upon engine type (spark-ignition or diesel) and operating characteristics, as well as on the specific conditions that exist at the time of measurement [61][62][63][64].…”
Section: Applications To Vehicle Emitted Particulatementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of particle morphology using electron microscopes have shown that individual particles emitted from diesel and spark-ignition engines exhibit fractal-like characteristics [59,60]. However, specific parameters of the fractal-like particles, such as fractal dimension and radius of gyration, are widely variable dependent upon engine type (spark-ignition or diesel) and operating characteristics, as well as on the specific conditions that exist at the time of measurement [61][62][63][64].…”
Section: Applications To Vehicle Emitted Particulatementioning
confidence: 99%
“…Similarly, optical particle counters are calibrated with aerosols composed of spherical particles and present results in terms of these calibrated particles. Cascade impactors measure particle aerodynamic diameter that is then converted to particle physical diameter by assuming that particles are spherical in shape, although often this is not the case for freshly emitted soot particles [60,74].…”
Section: Applications To Vehicle Emitted Particulatementioning
confidence: 99%
“…It is widely believed that motor vehicle PM is composed almost exclusively of solid soot, traces of ash and metals, sulfates, and semivolatile organics (Kittelson 1998). There is relatively little research on PM from spark-ignited (SI) engines because SI engines emit far less PM than diesel engines (Chakrabarty et al 2006;Dallmann and Harley 2010). However, SI engines, especially poorly maintained ones, can produce substantial PM emissions (Mazzoleni et al 2004) and may contribute disproportionately to urban PM exposures (Wu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The structure and size of these heterogeneous particles determines their optical and transport properties, which are an important, yet still uncertain, aspect of climate modeling, and also determines their toxicological effects via respiration [26,27]. However, transmission electron microscopy (TEM) and scanning transmission microscopy (STM) have the disadvantages of slow data collection, particle melting, and the need to capture the particle on a substrate [26]. XFELs have the unique opportunity to study large ensembles of this heterogeneous sample by taking individual measurements of each particle while still airborne.…”
Section: Methodsmentioning
confidence: 99%